Impact of climate change on soil erosion and sediment yield at Hilly Farms of Cameron Highlands, Malaysia - Nasidi, Nuraddeen Mukhtar (2020)
Soil erosion is one of the major environmental problems worldwide and is becoming serious limiting factor for crop production everywhere. It seriously impacts crop productivity by removing topmost soils and results into devastating almost irreversible damages. In Cameron Highlands, soil erosion has been a major environmental issue causing huge loss of agricultural soil and increasing rates of landslides. Recent studies and field surveys have reported that there is excessive soil erosion in Cameron Highlands with increasing risk of erosion-induced landslides and sedimentation of major water reservoirs. The purpose of this study was to project soil erosion and sediment yields to 2050s (2040-2069) and 2080s (2070-2099) under different climate change impact scenarios. The objective was also, to evaluate effectiveness of erosion control best management practices (BMPs) toward minimizing the potential soil erosion in Cameron Highlands using Global Circulation Models (GCMs) and four Representative Concentration Pathways (RCPs). To achieve this, precipitation datasets were obtained from World Data Center for Climate and downscaled using 30 years observed local precipitation data. intensity-frequency-duration (IDF) curves were constructed for current and future 2050s and 2080s scenarios. The rainfall trend was analyzed using Mann- Kendall and Sense’ slope tests at 5% significance level. Soil erosion was assessed using Revised Universal Soil Loss Equation (RUSLE) model. Moreover, soil erodibility (Kfactor) was developed through combination of field survey and existing soil series. Furthermore, crop management (C-factor) was established for current and future scenarios using Land Change Modeler (LCM) embedded in TerrSet software. Landsat 7 and 8 images were analyzed using IDRISI image processing software and simulated future land use scenarios by applying Markov Chain model. Furthermore, field experiments on erosion control BMPs were conducted at Cameron Highlands farm using three varieties of mustard crop (Green Apex 5502, Lucket 9116 and Little Princess 822) sown under both open and sheltered farms. The study revealed that performance of precipitation model indicated by KGE, NSE, RMSE, SE, MAE and MBE, are 0.64, 0.27, 1.25, 0.37, 1.63 and 0.15, respectively. The simulated precipitations were found to increase relative to baseline period by 6.8%, 12.9%, 20%, and 37% for 2050s; 16.1%, 28.6%, 39.2% and 42.3% for 2080s under RCP2.6, RCP4.5, RCP6.0 and RCP8.5 scenarios, respectively. Projected IDF curves were found greater than the baseline condition under 2, 5, and 20 years return periods. The highest erosivity (R-factor) of 6,039 MJ mm ha– 1 hr– 1 yr– 1 was found at Tanah Rata sub-catchment by 2080s under RCP8.5 scenario, which indicated 83% increase relative to baseline. Moreover, spatial variation of K-factor was found ranged from 0.00113 to 0.01613. The erosion projection showed that severe to extreme forms of soil erosion (>50 t ha-1) will occupy 12.44% of the study catchment, with highest annual soil loss of 1.71× 10 6 ton by 2080s under RCP8.5 scenario. Similarly, the corresponding severe sediment yields will be 243,061 t ha-1year-1 which represents 57.6% of total soil loss by 2080s under RCP8.5 scenario. Sediment Delivery Ratio (SDR) was computed as 0.208 which signifies the fraction of soil loss deposited outside the study watershed. The field experiments revealed highly significant effect of three BMPs (terracing, sediment trap and waste management) on sediment yields generation in both open and sheltered farms. It has been presented that, largest sediment yields of 13.9 ton/ha, 14.2 ton/ha and 14.5 ton/ha are collected from open farm control plots sown with Green Apex 5502, Lucket 9116 and Little Princess 822, respectively. However, the application of the control BMPs achieved high sediment reductions of 53.8%, 54%, and 52.3%, under terracing, sediment trap and waste management, respectively. In the other hand, the sheltered farm BMPs achieved more sediment reductions of 65.4%, 59%, and 53.8% under terracing, sediment trap and waste management, respectively. Additionally, the crop yield performance shows a significant effect of the varieties of mustard, but not with the types of farms, on total sediment yields. It is noted that, nutrients loss in the runoff is a crucial factor of crop cultivation, however, this study did not evaluate it due to complexity of the work. In general, the study simulated the impact of climate change on erosion and sediment yields at Cameron Highlands and revealed the effects of control BMPs under both sheltered and open farms. This information is essential toward reducing large amount of predicted soil loss due to effect of climate change and will support the management and policies makers to design effective soil conservation measures.